2021
DOI: 10.1111/gtc.12829
|View full text |Cite
|
Sign up to set email alerts
|

Di‐lysine motif‐like sequences formed by deleting the C‐terminal domain of aquaporin‐4 prevent its trafficking to the plasma membrane

Abstract: Aquaporin‐4 is a transmembrane water channel protein, the C‐terminal domain of which is facing the cytosol. In the process of investigating the role of the C‐terminal domain of aquaporin‐4 with regard to intracellular trafficking, we observed that a derivative of aquaporin‐4, in which the C‐terminal 53 amino acids had been removed (Δ271‐323), was localized to intracellular compartments, including the endoplasmic reticulum, but was not expressed on the plasma membranes. This was determined by immunofluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The cytoplasmic di-Lysine motifs shown to be involved in tra cking of protein to ER and plasma membrane in earlier studies [23,24] was observed at the N-terminus of transmembrane helices in 22…”
Section: Resultsmentioning
confidence: 94%
“…The cytoplasmic di-Lysine motifs shown to be involved in tra cking of protein to ER and plasma membrane in earlier studies [23,24] was observed at the N-terminus of transmembrane helices in 22…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, replacing the C‐terminal domain with the corresponding region of mAQP1 (Fig. 1A) influences the steady‐state subcellular localization of AQP4 [23]. These observations suggest that the C‐terminal domain of AQP4 plays a role in its trafficking to lysosomes after antibodies bind against its extracellular domains.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that deleting C‐terminal 53 amino acids also form a di‐lysine motif‐like sequence (Fig. 9A, Δ271–323) and prevents the mutant from localizing to the plasma membrane [23]. It should be noted that this mutant was quite stable and insensitive to protease inhibitors (Figs 2B,C (lane 5) and 7K,O), suggesting that a sequence implicated in destabilizing the protein exists between Gln 271 and Lys 313 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation